Radiological outcomes of PEEK rods in patients with lumbar degenerative diseases: A minimum 5-year follow-up - Huang, Weimin; Wang, Wenqiao; Xu, Xiaoduo; Wang, Lei; Wang, Jingming; Yu, Xiuchun (Frontiers in Surgery, 2023)
Abstract Purpose To determine the long-term radiological outcomes of PEEK rods in patients with lumbar degenerative diseases. Methods Radiological outcomes of cohort cases with lumbar degenerative diseases following PEEK rods were retrospectively studied. Disc height index (DHI) and range of motion (ROM) were measured by X-rays. The CT scans and reconstruction were used to determine screw breakage, rods fracture, screw loosening and intervertebral bony fusion status. The MRI scans were used to evaluate the changes of intervertebral discs at the non-fusion segments and adjacent segments in terms of Pfirrmann Classification. Results A total of 40 patients completed the mean of 74.8±9.6 months follow-up, with 32 patients undergoing hybrid surgery and 8 patients undergoing non-fusion surgery. The mean DHI changed from preoperative 0.34 to 0.36 at the final follow-up and the ROM declined from 8.8°preoperatively to 3.2°at the final visit, however, both had no statistical differences. Of the 40 levels underwent non-fusion procedure, 9 levels showed disc rehydration with 7 patients from Grade 4 to Grade 3 and 2 patients from Grade 3 to Grade 2. The other 30 cases did not show distinctive change. No screw loosening or rods breakage were detected during the follow-up periods. Conclusion PEEK rods have obvious protective effects on degenerated intervertebral disc of non-fusion segments and the incidence of complications related to internal fixation is low. PEEK rods pedicle screw system is safe and effective in the treatment of lumbar degenerative diseases.